2021
DOI: 10.1111/pan.14181
|View full text |Cite
|
Sign up to set email alerts
|

Lactated Ringer's solution versus normal saline in pediatric living‐donor liver transplantation: A matched retrospective cohort study

Abstract: Wan-bing Dai and Ling-ke Chen contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It was with keen interest that we read the article by Dai et al, "Lactated Ringer's solution versus normal saline in pediatric living-donor liver transplantation: A matched retrospective cohort study." 1 The authors found decreased patient mortality and graft morbidity in liver transplant patients resuscitated with normal saline compared to Lactated Ringer's.…”
Section: Use Of Normosol and Plasma-lyte For Pediatric Liver Transplantsmentioning
confidence: 96%
“…It was with keen interest that we read the article by Dai et al, "Lactated Ringer's solution versus normal saline in pediatric living-donor liver transplantation: A matched retrospective cohort study." 1 The authors found decreased patient mortality and graft morbidity in liver transplant patients resuscitated with normal saline compared to Lactated Ringer's.…”
Section: Use Of Normosol and Plasma-lyte For Pediatric Liver Transplantsmentioning
confidence: 96%
“…9,19 However, mortality rates were lower for patients who received NSS, compared with LR, during pediatric liver transplant operations. 20 Many studies in adults have not shown clinically meaningful differences in LR vs NSS. 21,22 For hospitalized children on the wards, there are no data to suggest that balanced or unbalanced IVFs are superior.…”
Section: Ivfsmentioning
confidence: 99%
“…Some data suggest that balanced fluids may be preferred for fluid resuscitation in the pediatric intensive care unit population 9,19 . However, mortality rates were lower for patients who received NSS, compared with LR, during pediatric liver transplant operations 20 . Many studies in adults have not shown clinically meaningful differences in LR vs NSS 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“….0%) and higher rates of early allograft dysfunction and primary nonfunction (19.7% and 11.5% vs. 3.3% and .0%, respectively) over the normal saline group. 51 In a study involving adult LDLT donors, LR was associated with hepatic dysfunction compared with Plasma-Lyte. 52 infusion compared with placebo.…”
Section: Intraoperative Fluid Of Choicementioning
confidence: 99%
“…Lactate in lactated ringer's solution (LR) could increase the lactate load to a newly perfused liver graft. In pediatric LDLT patients, a propensity‐score matched analysis comparing LR and normal saline for intraoperative volume replacement showed that the LR group had a higher 90‐day mortality rate (11.5% vs. .0%) and higher rates of early allograft dysfunction and primary nonfunction (19.7% and 11.5% vs. 3.3% and .0%, respectively) over the normal saline group 51 . In a study involving adult LDLT donors, LR was associated with hepatic dysfunction compared with Plasma–Lyte 52 .…”
Section: Essentials Of Anesthetic Management Of Ldlt Recipientsmentioning
confidence: 99%